Impact of Irrigation System on Malaria Transmission in Jazan Region, Saudi Arabia - Mohammed Hassan Alzahrani; Philip McCall; Amir Hassan; Abdiasiis Ismael Omar; Abdelmohsin Mohammed Abdoon (Open Journal of Tropical Medicine - Peertechz Publications, 2017)
Introduction: Jazan Region, in the Southwestern Saudi Arabia is known as the mostly affected region with malaria. Malaria occurs at hypo-to hyperendimic level where P. falciparum is the commonest parasite and An. arabiensis is the principal vector. Different types of crop irrigation systems were often blamed for aggravating the health risks of local communities. Reservoirs, irrigation canals, and dams are closely  ssociated with vector-borne parasitic diseases. Thus, seasonal transmission period of a disease such as malaria may be extended as a result of these irrigation systems. The present study is meant to investigate vector breeding and transmission sites associated with the irrigation system in Jazan area for malaria through vector sampling and direct observation. Methods:The study was conducted in three villages in irrigated and three villages in non-irrigated areas in Jazan Region. Entomological surveys were conducted over 12 months from January to December 2004. Larvae were sampled by standard dipping technique and adults were sampled by pyrethrum knockdown collection and CDC light traps. Anopheline mosquitoes were morphologically identified and further verified at the Natural History Museum, London, UK. Mosquito blood meals were tested by direct enzyme linked immune sorbent assay technique for source identification. Results: Of the 3498 anophelines larvae collected, during this study, 53.2% were from the irrigated sites. The total collection of larvae revealed the prevalence of 7 Anopheles spp., of these An. d`thali and An. pretoriensis were the most abundant, and comprised about 50.77 % and 36.91%, of the total collection, respectively. Larvae of the known malaria vector, An.arabiensis comprised 9.43% (330), of which, 69.4%were harvested from habitats at the irrigated area. A total of 2938 adult anophelines were caught from both areas and 1539 (52.4%) were An. d`thali, An. multicolor and An. arabiensis from irrigated area. A total of 106 blood-meal specimens from An. d`thali and An. arabiensis females, were examined and 95.3% were of human origin. Discussion and Conclusion: Of the seven anopheline species encountered, An.sergentii, An. multicolor and An. fluviatilis are fi rst record in Jazan Region. The study showed no significant difference between irrigated and non-irrigated areas can provide mosquitoes with various breeding habitat types. The known malaria vector in the region, An. arabiensis were more abundant in irrigated areas as larvae (69.3%) and as adults (69.4%) and together with An. d`thali showed high tendency towards anthropophagic behaviour (95.33%).